Determinan Pendapatan Pekerja Wanita Sektor Informal di Desa Baturiti Kabupaten Tabanan - Wiggers, Maya Patricia; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
Tabanan Baturiti village, one of the largest villages in the district population Baturiti. Women in the village helped men to work, especially in the informal sector (agriculture, trade and craftsmen) The purpose of this study was to determine the amount of income informal sector women workers, as well as the influence of age, education, working capital and time allocation simultaneously and partially on the income of women workers in the informal sector Baturiti village. In this study were taken 90 respondents, the extraction is carried out by quota sampling. Further analysis of data using multiple linear regression analysis technique. The variables of age, education, working capital, and allocation waktudapat explain 95.9 percent change in income. Among the four independent variables, it appeared that the working capital has the most dominant influence on female labor income variable. Based on these findings it can be suggested that in order to increase the income of women workers, the working capital loans that are distributed to women workers.
Keywords: income, age, education, working capital, and time allocation